Summer Sounds - Bentley, Marla (United Kingdom Cambridge University Press, 2010)
Katy is reluctantly at a children's camp for the summer. She thinks she's too old to be with a hundred strangers. But soon it becomes clear that something strange is happening to the other children at the camp. What is it? And why aren't Katy and her new friend Riley affected?
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents
Keywords: Adventure; Language Learning; Reading books; Beginner/Elementary level